1987
DOI: 10.1210/jcem-64-4-669
|View full text |Cite
|
Sign up to set email alerts
|

Ultradian Oscillations of Plasma Glucose, Insulin, and C Peptide in Man During Continuous Enteral Nutrition

Abstract: The profiles of plasma glucose, insulin, and C-peptide were studied in normal men receiving continuous enteral nutrition. Large oscillations occurred with periods of 53-113 min. Their mean amplitudes, expressed as a percentage of the 24-h mean, were as high as 20% for glucose, 54% for insulin, and 56% for C-peptide. The oscillations of plasma insulin levels throughout the 24 h were concomitant with those of C-peptide. Rapid 8- to 14-min plasma insulin and glucose oscillations were smaller in magnitude and coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
90
0
1

Year Published

1987
1987
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(96 citation statements)
references
References 29 publications
5
90
0
1
Order By: Relevance
“…The glucose oscillations, varying in number in each subject, display a periodicity of 51 to 112 min, which is similar to that previously described in man during continuous enteral nutrition [8]. The oscillations amplitude is highest immediately after meals, decreasing and becoming less regular with time, especially during the night.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The glucose oscillations, varying in number in each subject, display a periodicity of 51 to 112 min, which is similar to that previously described in man during continuous enteral nutrition [8]. The oscillations amplitude is highest immediately after meals, decreasing and becoming less regular with time, especially during the night.…”
Section: Discussionsupporting
confidence: 83%
“…We recently described the existence of 53-113 min oscillations of plasma glucose, insulin and C-peptide levels in man during continuous enteral nutrition [8]. This study was designed to establish whether similar oscillations occur in the postprandial state.…”
mentioning
confidence: 99%
“…Through biological experiments it has been well-established [6,9,17,18] that insulin secretion in the pancreas oscillates on a number of different time scales, ranging from tens of seconds to more than 100 minutes. The oscillations with larger period (80-150 mins) are known as ultradian oscillations and a model developed by Sturis et al [19] (see also Keener & Sneyd [7]) provides a possible mechanism for their origin.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that the majority, if not all, of normal insulin secretion occurs as pulsatile bursts (5,6). In healthy humans, high-frequency insulin concentration pulses recurring at intervals between 6 and 13 min have been reported (4,6) along with oscillations of larger amplitude and a longer periodicity of ~120 min (7,8). The cellular mechanisms that generate and regulate oscillatory insulin secretion by the ␤-cell are elusive, although a pivotal role of phosphofructokinase M has been suggested recently (9,10).…”
mentioning
confidence: 99%